1981
DOI: 10.1021/jm00140a020
|View full text |Cite
|
Sign up to set email alerts
|

Gastric antisecretory agents. 2. Antisecretory activity of 9-[(aminoalkyl)thio]-9H-xanthenes and 5-[(aminoalkyl)thio]-5H-[1]benzopyrano[2,3-b]pyridines

Abstract: A series of 9-[(aminoalkyl)thio]-9H-xanthenes (3-6) and 5-[(aminoalkyl)thio]-5H-[1]benzopyrano[2,3-b]pyridines (7-10) possessing gastric antisecretory activity in the rat and dog is described Many of the compounds possessed good activity in the pylorus-ligated rat and several inhibited histamine-stimulated gastric acid secretion in the dog. The mechanism of acid secretion inhibition is not related to anticholinergic or histamine (H2) receptor antagonism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…We then synthesized 3,5-bis((E)-4-bromobenzylidene)-1-methylpiperidin-4-one 7h from the reaction of 5 and p-bromobenzaldehyde following literature procedure [44]. Subsequently, the reaction of 7h and cyclohexane-1,3-dione 8a affording chromeno [3,2-c] [1][2][3][4][5]. We then tried this reaction in acidic conditions and observed that in the presence of p-tolunesulfonic acid the reaction afforded 9h in a moderate yield of 45 % (Scheme 4, entry 7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We then synthesized 3,5-bis((E)-4-bromobenzylidene)-1-methylpiperidin-4-one 7h from the reaction of 5 and p-bromobenzaldehyde following literature procedure [44]. Subsequently, the reaction of 7h and cyclohexane-1,3-dione 8a affording chromeno [3,2-c] [1][2][3][4][5]. We then tried this reaction in acidic conditions and observed that in the presence of p-tolunesulfonic acid the reaction afforded 9h in a moderate yield of 45 % (Scheme 4, entry 7).…”
Section: Resultsmentioning
confidence: 99%
“…Found: C,81.23;H,6.40;N,3.75 %. -2methyl-3,4,6,7,8,10-hexahydro-1H-chromeno [3,2c] 5,27.6,36.9,44.6,54.4,55.0,119.9,126.3,127.3,127.8,128.5,128.6,129.4,129.6,130.0,130.4,133.5,134.1,133.5,134.1,134.7,139.9,166.4,196.9. Anal.…”
Section: General Experimentalmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of structurally relevant biologically active compounds are benzopyranopyridines B, found to inhibit mitogen-activated protein kinase-activated protein kinase 2 and attenuate the production of pro-inflammatory TNFα, 12 and C, reported to inhibit histamine-stimulated gastric acid secretion in animals. 13 We previously disclosed a one-step three-component synthesis of 3,5-dicyanopyridines D starting from various aldehydes, thiols and malononitrile (Fig. 2).…”
mentioning
confidence: 99%